Image analysis optimization for nanowire-based optical detection of molecules - Davtyan Rubina; Anttu Nicklas; Valderas-Gutiérrez Julia; Höök Fredrik; Linke Heiner (Nanophotonics)
Semiconductor nanowires can enhance the signal of fluorescent molecules, thus significantly improving the limits of fluorescence detection in optical biosensing. In this work, we explore how the sensitivity can further be enhanced through “digital” detection of adequately spaced vertically aligned nanowires, employing single-emitter localization methods, and bright-field microscopy. Additionally, we introduce a systematic analysis pipeline aimed at harnessing this digital detection capability and evaluate its impact on detection sensitivity. Using a streptavidin-biotin assay, we demonstrate that single-emitter localization expands the dynamic range to encompass five orders of magnitude, enabling detections of concentrations ranging from 10 fM to 10 nM. This represents two to three orders of magnitude improvement in detection compared to methods that do not utilize single-emitter localization. We validate our analysis framework by simulating an artificial dataset based on numerical solutions of Maxwell’s equations. Furthermore, we benchmark our results against total internal reflection fluorescence microscopy and find, in time-resolved titration experiments, that nanowires offer higher sensitivity at the lowest concentrations, attributed to a combination of higher protein capture rate and higher intensity per single protein binding event. These findings suggest promising applications of nanowires in both endpoint and time-resolved biosensing.